Strategi Murabbi dalam Meningkatkan Kemampuan Membaca Al-Qur’an Mahasantri - nilawati, Febri; Rini, Rini; Ratnawati, Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the murabi strategy in improving the ability to read Al-Qur'an mahasantri Ma'had Al-Jami'ah IAIN Curup batch 2019. This research is a qualitative study to try to extract information from Murabbi and Murabbiyah. The results of the research, first, become Murabbi's strategy in improving the ability to read Al-Qur'an Mahasantri, namely by using a strategy of grouping students (classical) based on Al-Qur'an reading skills and sorogan strategy to improve the ability to read Al-Qur'an Mahasantri. The two criteria for success are reading the Koran according to the principles of Tajweed Science properly and correctly, doing ablution and prayer properly and correctly, memorizing prayer readings, memorizing Juz 30, understanding the basics of Akidah and Morals and understanding ethics (adab), memorizing selected Surahs, attendance in the study of the Koran. The three supporting and inhibiting factors for Murabbi in improving the ability to read the Al-Qur'an Mahasantri, which are the supporting factors for murabbi in improving the ability to read the Koran, are the role and attention of the board as well as the interest and motivation that grows from the students themselves while those who become The inhibiting factors for murabbi in improving the ability to read the Koran are limited time and limited facilities and infrastructure that trigger the strategy to be obstructed. In conclusion, the strategy used by Murabbi in improving the ability to read the Al-Qur'an Mahasantri Ma'had Al-Jami'ah IAIN Curup Class of 2019 is to use a grouping strategy (classical) based on the ability to read the Koran and the sorogan strategy to improve their abilities. read the Qur'an Mahasantri. Keywords: Murabbi, Reading Al-Qur'an, learning strategies.